Teacher empowerment and cultural context the case of Brunei Darussalam - Thomas, Shanthi (Routledge series on schools and schooling in Asia, 2018)
Teacher empowerment is a psychological and socio-structural motivational process that enhances teacher performance and self-expression. This book treads new ground by redefining Teacher Empowerment in the cultural context of South East Asia. Using the case of Brunei Darussalam which has a unique socio-cultural make-up as a melting pot of Malay, Chinese and other Asian cultures, the book offers a unique insight how the Teacher Empowerment dynamics is played out in this context.